2021
DOI: 10.1007/s12144-021-02188-3
|View full text |Cite
|
Sign up to set email alerts
|

A study on the relationship between shame, guilt, self-criticism and compulsive sexual behaviour disorder

Abstract: There is evidence that compulsive sexual behaviour (CSB) and problematic pornography use (PPU) can be associated with selfcriticism, shame and guilt. The aim of the current study was to investigate further these relationships. Study 1-Participants were 121 adults, mean age 26.82 years (18-45), 58 males and 63 females. They filled in a demographic questionnaire, the Hypersexual Behaviour Inventory (HBI), self-criticizing/attacking and self-reassuring scale (FSCRS) and the Test of Self-Conscious Affect, (TOSCA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Internal factors, such as self-disgust, self-criticism (Zahn et al, 2015 ), and shame proneness have been found to be associated with anger suppression and conflict avoidance (Cheung and Park, 2010 ) as well as with subsequent anger outbursts (Alia-Klein et al, 2020 ). In addition, structural equation modeling showed that self-criticism predicted shame and guilt, which, in turn, predicted problematic dysfunctional outcomes such as addiction and problematic behavior (Sassover et al, 2021 ; Snoek et al, 2021 ). It has been proposed that anger may be an emotion supporting goal-directed behavior when an environmental situation prevents the desired goal to be fulfilled, causing frustration (Panksepp, 2005 ).…”
Section: Hierarchical Emotional Responses: a Polyvagal Perspective On...mentioning
confidence: 99%
“…Internal factors, such as self-disgust, self-criticism (Zahn et al, 2015 ), and shame proneness have been found to be associated with anger suppression and conflict avoidance (Cheung and Park, 2010 ) as well as with subsequent anger outbursts (Alia-Klein et al, 2020 ). In addition, structural equation modeling showed that self-criticism predicted shame and guilt, which, in turn, predicted problematic dysfunctional outcomes such as addiction and problematic behavior (Sassover et al, 2021 ; Snoek et al, 2021 ). It has been proposed that anger may be an emotion supporting goal-directed behavior when an environmental situation prevents the desired goal to be fulfilled, causing frustration (Panksepp, 2005 ).…”
Section: Hierarchical Emotional Responses: a Polyvagal Perspective On...mentioning
confidence: 99%
“…Guilt/Shame/Relief (35%): The most frequent MR included associations of diffuse concepts, such as “guilt”, “shame”, “weakness”, “anxiety” and “frustration” which suggests generalized representations not limited to the psychoactive substance or potentially addictive behavior. Guilt has been described previously as a primary affective response in case of alcohol and other substance use disorders [ 41 ], tobacco use [ 42 ], problematic social networking site use [ 43 ] and compulsive sexual behavior and problematic pornography use [ 44 48 ]. Both “shame” and “guilt” were frequent associations, suggesting that the suspected view upon the self of others and self-reviewing and self-judgment can be crucial mechanisms [ 49 ], either restricted to the addiction–guilt -, or generalized to self-identity–shame–[ 41 ], but not differentiated strictly among individuals’ MRs.…”
Section: Discussionmentioning
confidence: 99%
“…In previous study, teenagers scored higher on mood modification than other factors of PPU ( Bőthe, Vaillancourt-Morel, et al., 2021 ), and one of their main motivations for online sexual experience was mood management ( Castro-Calvo, Giménez-García, Gil-Llario, & Ballester-Arnal, 2018 ). Combining with the high score in moral incongruence, the finding may suggest that there could be a cyclical pattern of pornography use: pornography use may decrease the stress and modify the negative mood, but adolescents may encounter shame, regret, and self-accusation ( Sassover et al., 2021 ), which results in more pornography use to escape shame and guilt. However, these potential hypotheses warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%